Perancangan Video Promosi Cat Aksritex Menggunakan Media YouTube - Zulfiqar Bima Bagaskara; Putra Uji Deva Satrio (Jurnal Ilmu Komputer dan Desain Komunikasi Visual, 2019)
Aksritex paint is one of the textile paints. It was originally created by Ms. Nanik (an art teacher) in 2017. Aksritex paint was first promoted through "person to person", that the information was less spread to the public. In 2017, some researchers conducted a survey in Sidoarjo which resulted in Aksritex brand awareness of paint being very low in the Sidoarjo community. This research used the method of General Visual Communication Design 2 taken from the book "Integrated Visual Communication Design by Yongky Safanayong. The research procedure were data collection, analysis, synthesis, themes, communication strategies, visualization, production and final results. After making a promotional video, it was then uploaded to YouTube. Lastly, the researchers conducted a sampling of the target audience in Sidoarjo in order, to test the interest of the target audience for the Promotional video of Aksritex paint. After gaining the data, this researh showed that the average target audience's response to the Aksritex paint promotional video was valid. So it can be concluded that researchers have succeeded in increasing brand awareness of Aksritex paint products through promotional videos on YouTube. This was supported by other questions that discussed about the video such as color, typography, transitions and effects of the video, and almost all answers of the target audience are valid. Keywords — Aksritex Paint, Brand awareness, and Promotional Videos